The Ludovisi "throne", the Boston "throne" and the Warren Cup: retrospective works of forgeries? - Siri Sande (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2018)
The Ludovisi and Boston "thrones" are among the most discussed monuments in the history of art. It is here argued that certain details on the "thrones" find their closest parallel artifacts of the Augustan period such as decorative reliefs and candelabra, Arretine ware and silver work: notably the so-called Warren cup in the British Museum. The "thrones" cannot, therefore, be dated to the early Classical period. But does that mean that they are Roman retrospective works? Both the "thrones" and lately also the Warren cup have been regarded by some scholars as forgeries. The author of this article strongly suspects that all three were created in the late 19th century.